2023
DOI: 10.3390/mi14020322
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of a Hybrid Displacement Amplifier Supporting a High-Performance Piezo Jet Dispenser

Abstract: In this study, a compliant amplifier powered by a piezoelectric stack is designed to meet high−performance dispensing operation requirements. By studying the issue of low frequency bandwidth on the traditional bridge−type amplifier mechanism, we propose a displacement amplifier mechanism, hybrid bridge−lever−bridge (HBLB), that enhances its dynamic performance by combining the traditional bridge−type and lever mechanism. A guiding beam is added to further improve its output stiffness with a guaranteed large am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This results in a constraint that negatively affects the achievement of a significant output displacement for the compliant stages. Consequently, a number of displacement amplifiers were created to enhance the output displacement of developed mechanisms, such as an L-shape lever [15], a hybrid rhombus lever [16], a double lever [17], a single lever [18], a symmetric four-lever [19], a hybrid bridge-lever-bridge [20], and a hybrid bridge-Scott-Russell mechanism [21].…”
Section: Introductionmentioning
confidence: 99%
“…This results in a constraint that negatively affects the achievement of a significant output displacement for the compliant stages. Consequently, a number of displacement amplifiers were created to enhance the output displacement of developed mechanisms, such as an L-shape lever [15], a hybrid rhombus lever [16], a double lever [17], a single lever [18], a symmetric four-lever [19], a hybrid bridge-lever-bridge [20], and a hybrid bridge-Scott-Russell mechanism [21].…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric ceramic is a transducer that transforms electrical energy into mechanical energy [ 1 , 2 , 3 ]. It has characteristics of high resolution, fast response, high stiffness, little magnetic interference, and little heat generation, making piezoelectric ceramic advantageous over conventional actuators in precise applications [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations have shown that research on static modeling of the compliant-amplifying mechanism has attracted a great deal of attention, and the methods used [ 18 ] mainly include Castigliano’s second theorem [ 2 , 19 , 20 , 21 , 22 ], the flexibility matrix method [ 23 , 24 , 25 , 26 , 27 , 28 ], the matrix displacement method [ 1 , 29 , 30 ], the elastic beam theory [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ], and kinematic principles [ 35 , 38 , 39 , 40 , 41 , 42 ]. Based on these methods, the effects of the main parameters of the mechanism on its static characteristics have been analyzed, and the relationship between the input and output displacements of the mechanism was established.…”
Section: Introductionmentioning
confidence: 99%